Efeitos de formulações contendo Clomazone® sobre parâmetros bioquímicos, citogenéticos e comportamentais em peixe-zebra (Danio rerio) - Cruz, Taisson Kroth Thomé da (2020)
The largest consumer of pesticides in the world since 2009, Brazil, consumed around 84% of the pesticides sold in Latin America. The increase in consumption, as well as the reduction of riparian forests, together with indiscriminate use, can lead to contamination of the soil, water and non-targets of these pesticides. Clomazone®, belongs to the herbicide class, used to control preemergent pests. The exacerbated use of pesticides can cause an imbalance in the production of reactive species, which can trigger a series of problems, including behavioral changes, oxidative and enzymatic damage, as well as damage to DNA and RNA. In this sense, research on the effects of this pesticide using alternative models such as zebrafish, are extremely relevant in scientific circles, considering that this work is, until then, a pioneer in the relationship between adult zebrafish versus Clomazone® / Gamit360CS®. To assess the potential toxicological risks of Clomazone® and Gamit360CS®, the animals were exposed to five different concentrations (0.5; 1.0; 2.5; 5.0 and 10.0 mg / L-1), by a 96h period, in addition to the control group that was not exposed. For the micronucleus analysis, blood tissue was used, with the smear technique, the behavioral analyzes, the animals were individually conditioned in the light-dark apparatus, where the following behavioral parameters were observed: latency between the areas, time in the dark, transitions between the areas of the apparatus and risk assessment. A decrease in AChE levels was observed in brain tissue, in tissue. In GST levels, in brain and gill tissue there was an increase in levels, in muscle tissue GST showed uneven results. Regarding oxidative damage, lipid peroxidation, there was an increase in brain tissue, whereas in branchial tissue there was a significant increase, especially when exposed to 10.0 mg / L-1, in muscle tissue there was no significant difference in the results. As for the levels of non-protein thiols, no difference in results was observed in all tissues examined. The behavioral tests showed results of anxiety-like behavior, as there was an increase in latency between the areas of the apparatus, there was an increase in the scototaxis of two groups exposed to the herbicide, as well as an increase in risk exploitation in an exposed group. Genotoxicity tests for micronucleus were found to be within the normal range for micronucleus, but several nuclear anomalies of the Cariorrexe type, indicating a high genotoxicity of Gamit360CS®. We can conclude that both Clomazone® and Gamit360CS® have toxicity levels. Thus, the objective of this dissertation was to verify the toxicity and genotoxicity of the herbicide Clomazone® and Gamit360CS®, using zebrafish as an experimental organism. For that, it was analyzing behavioral data, antioxidant activity of enzymatic and non-enzymatic molecules, and, lipid damage.